An Experimental Assessment of Iraqi Local Cement and Cement Slurry Design for Iraqi Oil Wells Using Cemcade - Assi, Amel Habeeb; Almehdawi, Faleh H.M. (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
This effort is related to describe and assess the performance of the Iraqi cement sample planned for oil well-cementing jobs in Iraq. In this paper, major cementing properties which are thickening time, compressive strength, and free water in addition to the rheological properties and filtration of cement slurry underneath definite circumstances are experimentally tested. The consequences point to that the Iraqi cement after special additives encounter the requests of the API standards and can consequently is used in cementing jobs for oil wells. At this research, there is a comparative investigation established on experimental work on the effectiveness of some additives that considered as waste materials which are silica fume, bauxite, and glass powder, and other conventional additives which are: (SCR -100 Retarder, HR-5, FWCA, Hollow Glass Spheres (HGS) and Halad-9) that currently used in our fields on local Iraqi cement and putting foreign cement results as a governor. Chemical analysis for Iraqi cement, imported cement, and waste materials samples was determined using the X-ray fluorescence (XRF) technique and found minor differences in composition between those samples and depending on the results of X-ray, we selecting the appropriate additives to prepare cement slurry samples. The X-ray fluorescence (XRF) results show that Iraqi Cement has a low value of silica which is about 18.63% while Omani cement about 37.58%. This research examined the potential of micro silica, bauxite, and waste glass powder to produce sustainable cement slurry. The results showed that adding micro silica and bauxite enhances the performance of Iraqi cement but also leads to a slight decrease in thickening time. To avoid this problem, Superplasticizer is used to make the process of cement pumping more easily, in other words, increase thickening time and increase compressive strength. Furthermore, adding glass powder increase the value of compressive strength. Both additives (waste and conventional) are used for the slurry design for achieving better slurry properties, but waste additives increase and enhance Iraqi cement performance than conventional additives, in other words, making it more effective than commercial cement. Depending on the results of the compressive strength test, the optimal concentration of the waste materials used in this research was found, and then the optimal concentration was used to prepare cement samples. The results showed that the use of waste materials to prepare cement slurry is a promising way to improve the efficiency of cement work and to reduce the negative environmental impact resulting from the industry. The results of the program CemCADE proved to be the sample A and C showed good performance through high cement bonding and ideal distribution of fluids designed to accomplish the cementing process.